The metagenomics of soil bacteria and fungi and the release of mechanical dormancy in hard seeds - Wu, Yu; Sun, Xiao-Rui; Pritchard, Hugh W.; Shen, Yong-Bao; Wu, Xiao-Qin; Peng, Chen-Yin (Frontiers in Plant Science, 2023)
Persistence in the soil is a function of seed physiology, particularly non-germination and inherent lifespan. However, for seeds with mechanical dormancy, non-germination is also a function of the composition and activity of the soil microbiota. We attempted to screen out microorganisms in the soil that can specifically and rapidly decompose the hard fruit pericarps of Tilia miqueliana Maxim., a unique native tree species in China. Using the classical replica plating method, more than 100 different culturable microorganisms that could rapidly erode the pericarp were collected from the surface of pericarps under different culture conditions. At the same time, we successfully extended the concept of metagenomics and applied it to the identification of mixed artificial cultures. The decomposition process of the pericarps in soil was also simulated artificially. The physical and chemical data suggested a potential mechanism of microbial scarification and cracking in pericarp, whilst the embryos inside the eroded fruits retained good viability. The findings of this research can inform the design of experiments on the seed ecology of persistence.